The Silver, Cobalt, Chromium, Iron, Mercury, Rubidium, Antimony, Selenium, and Zinc Contents in Human Bone Affected by Chondrosarcoma - Vladimir, Zaichick; Sofia, Zaichick (Journal of Hematology and Oncology Research, 2015)
Objectives: To clarify the role of trace elements in the etiology and the pathogenesis of the chondrosarcoma, a non-destructive neutron activation analysis with high resolution spectrometry of long-lived radionuclides were performed. Methodology: The silver (Ag), cobalt (Co), chromium (Cr), iron (Fe), mercury (Hg), rubidium (Rb), antimony (Sb), selenium (Se), and zinc (Zn)mass fractions and Co/Zn, Cr/Zn, Fe/Zn, Hg/Zn, Sb/Zn, Co/Rb, Cr/Rb, Fe/Rb, Hg/Rb, Sb/Rb, and Se/Rb mass fraction ratios were estimated in normal bone samples from 27 patients with intact bone (12 females and 15 males, aged from 16 to 49 years), who had died from various non bone related causes, mainly unexpected from trauma, and in tumor samples, obtained from open biopsies or after operation of 16 patients with chondrosarcoma ((3 females and 13 males, 8 to 65 years old). The reliability of difference in the results between intact bone and chondrosarcoma tissues was evaluated by Student’s t-test. Key Results: In the chondrosarcoma tissue the mass fractions of Co, Fe, and Se are significantly higher while the mass fraction of Rb is lower than in normal bone tissues. Moreover, significantly higher Co/Zn, Fe/Zn, Co/Rb, Cr/Rb, Fe/Rb, Sb/Rb, and Se/Rb mass fraction ratios are typical of the chondrosarcoma tissue compared to intact bone. In the chondrosarcoma tissue many correlations between trace elements found in the control group was no longer evident. Major Conclusions: In chondrosarcoma transformed bone tissues the trace element homeostasis is significantly disturbed.
Keywords: Trace element contents; trace element mass fraction ratios; human bone; chondrosarcoma; neutron activation analysis